PET/CT Poorly Predicts AJCC 8th Edition Pathologic Staging in HPV‐Related Oropharyngeal Cancer. (11th January 2021) - Snyder, Vusala; Goyal, Lindsey K.; Bowers, Eve M. R.; Kubik, Mark; Kim, Seungwon; Ferris, Robert L.; Johnson, Jonas T.; Duvvuri, Umamaheswar; Gooding, William E.; Branstetter, Barton F.; Rath, Tanya J.; Sridharan, Shaum S.
Abstract : Objective: The American Joint Committee on Cancer (AJCC) 8th edition introduced distinct clinical and pathological staging paradigms for human papilloma virus positive (HPV+) oropharyngeal squamous cell carcinoma (OPSCC). Treatment planning for OPSCC often utilizes positron emission tomography/computed tomography (PET/CT) to assess clinical stage. We hypothesize that PET/CT will accurately predict final pathologic AJCC 8th edition staging in patients with HPV+ OPSCC. Methods: All patients with primary HPV+ OPSCC with preoperative PET/CT who underwent transoral robotic surgery and neck dissection between 2011 and 2017 were identified. Data were collected via chart review. Two neuroradiologists performed blinded re‐evaluation of all scans. Primary tumor size and cervical nodal disease characteristics were recorded and TNM staging was extrapolated. Cohen's kappa statistic was used to assess interrater reliability. Test for symmetry was performed to analyze discordance between radiologic and pathologic staging. Results: Forty‐nine patients met inclusion criteria. Interrater reliability was substantial between radiologists for nodal (N) and overall staging (OS) (κ = 0.715 and 0.715). Radiologist A review resulted in identical OS for 67% of patients, overstaging for 31%, and understaging for 2%. Radiologist B review resulted in 61% identical OS, 39% overstaging, and 0% understaging. In misclassified cases, the test of symmetry shows strong bias toward overstaging N stage and OS ( P < .001). Radiologic interpretation of extracapsular extension showed poor interrater reliability (κ = 0.403) and poor accuracy. Conclusion: PET/CT predicts a higher nodal and overall stage than pathologic staging. PET/CT should not be relied upon for initial tumor staging, as increased FDG uptake is not specific for nodal metastases. PET/CT is shown to be a poor predictor of ECE. Level of Evidence: 4 Laryngoscope, 131:1535–1541, 2021